Abai’s poems in the paradigm of metapoetics - Aimukhambet Ж.Ә. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2021)
The article examines Abai’s poetic nature and literary skills, his individuality as a creative person in the paradigm of metapoetics. The nature of literary creativity, the mastery of the poet, the poetic language of his literary works were studied on the basis of conclusions of literary scholars as the main research directions of metapoetics. It is general knowledge that metapoetic analysis, based on the search for a creative personality in the text and thereby determining its identity, opens the way to new conclusions. In this context, there were analyzed Abai’s poetic texts, characterizing his poetic nature, literary nature and aesthetic vision. Using the example of the poet’s poems, which represent the idea of the essence, function of the art of words, their place in the spiritual and cultural knowledge, it is proposed to characterize them with the concepts “poetological poem”, “theory in a poem” and “theoretical poem”. In the process of analyzing poetic texts, the author highlights the issues of the creative process, inspiration, interweaving of thoughts and feelings, emotions that reflect the nature of the artist.